Self-consistent method for optimization of parameters of diode temperature sensors - Kulish, N.R.; Shwarts, Yu.M.; Borblik, V.L.; Venger, Ye.F.; Sokolov, V.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 1999)
In the framework of the diffusion transport model through an abrupt asymmetric p n-junction, the ideality factor of which is assumed to be equal to unity, and with the help of criteria commonly used to describe theoretically the semiconductor diode structures, the relations are obtained for estimation of parameters of the diode temperature sensor. The set of these parameters provides either the maximum extent of a thermometric characteristic toward the higher temperature range, or maximum sensitivity of the diode temperature sensor. For Ge, Si, GaAs diode temperature sensors with n⁺p- and р⁺n- junctions the limits of thermometric characteristics were determined, together with temperature dependencies of sensitivity, static and dynamic resistance calculated for cases of the maximum length of the thermometric characteristic and of maximum sensitivity. It has been shown that experimentally measured characteristics of diode temperature sensors are within the ranges determined by the limiting characteristics. The ways of further improvement of diode temperature sensors are discussed.